Taḥlīl al-Akhtā’ al-Naḥwiyyah fī Qirā’ah al-Nuṣūṣ al-‘Arabiyyah litilmīḋāt bi al-Ma’had: Analysis of Arabic Grammatical Errors in Reading Arabic Texts for Students at Islamic Boarding Schools - Safitri, Diana; Aisa, Aufia (Aphorisme: Journal of Arabic Language, Literature, and Education, 2022)
This study aimed to identify and explain the types of errors in reading Arabic text that the fourth-grade students of KMI studied at Pondok Modern Arrisalah Ponorogo. This research is qualitative with a case study model. The research data is in the form of errors in reading Arabic text. Data collection techniques were carried out by observation and documentation. At the same time, the data analysis was carried out by identifying Arabic text reading errors, grouping Arabic text reading errors, and analyzing Arabic text reading errors. The study's results stated that reading errors in Arabic text were grouped into grammatical, morphological, and phonological errors. The mistakes in reading Arabic texts amounted to 29 errors; 13 in the form of Arabic grammatical errors, 13 in the form of Arabic morphological errors, and 3 in the form of Arabic phonological errors. It was carried out to minimize the mistakes in reading Arabic text in class IV KMI at Pondok Modern Arrisalah Ponorogo; the teacher provides Arabic grammar learning enrichment consistently, repeats learning, and chooses a more appropriate Arabic learning method.